Konsep Peserta Didik Dan Tenaga Kependidikan Kelompok Bermain - widianti, maya; Aprilia Saputri, Maya; Nihwan (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2023)
Abstract: This article reviews the Concepts and Characteristics of Students and Education Personnel. In the Law of the Republic of Indonesia number 20 of 2003 concerning the National Education System chapter 1 article 1 it is stated that the educational workforce is a member of the community who is dedicated and appointed to support the implementation of education. As individuals who are growing and developing, students need consistent guidance and direction towards the optimal point of their natural abilities. The purpose of writing this article is to find out the Concepts and Characteristics of Students and Education Personnel in Playgroup Management. Learners in the play group are children aged 2-4 years who are trying to develop their potential through a learning process on a non-formal path. Early childhood educators or education personnel in quality play groups must meet academic qualifications and have the required potential. Keywords: Concepts, Characteristics, Students, Education Personnel, Playgroups.